2021
DOI: 10.1186/s12879-021-06958-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of visceral fat on the prognosis of coronavirus disease 2019: an observational cohort study

Abstract: Background Clarification of the risk factors for coronavirus disease 2019 (COVID-19) severity is strongly warranted for global health. Recent studies have indicated that elevated body mass index (BMI) is associated with unfavorable progression of COVID-19. This is assumed to be due to excessive deposition of visceral adipose tissue (VAT); however, the evidence investigating the association between intra-abdominal fat and COVID-19 prognosis is sparse. We therefore investigated whether measuring … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 38 publications
(35 reference statements)
1
21
0
Order By: Relevance
“…[ 20 ] underline that BMI poorly reflects actual body fat excess, whereas waist circumference better describes obesity. This issue should be more appropriately investigated as it has already been reported that a higher ratio of visceral fat in relation to total adipose tissue was superior to BMI also in predicting COVID-19 morbidity and mortality [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] underline that BMI poorly reflects actual body fat excess, whereas waist circumference better describes obesity. This issue should be more appropriately investigated as it has already been reported that a higher ratio of visceral fat in relation to total adipose tissue was superior to BMI also in predicting COVID-19 morbidity and mortality [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in a population with a high obesity prevalence, young individuals are more severely affected than is generally thought [ 69 ]. And there are now several systematic reviews and meta-analysis concluding that overweight and obesity is an important risk factor for COVID-19 severity [ 21 , 70 , 71 , 72 , 73 ], especially when it is characterized by excessive visceral adipose tissue [ 73 , 74 , 75 , 76 ].…”
Section: Risk Factors For Severe Covid-19mentioning
confidence: 99%
“…Recent literature data suggest that in addition to the well-established association between BMI-based obesity and severe COVID-19 outcome, the body fat distribution is also important; in particular, visceral adipose tissue and upper abdominal circumference have been proposed as simple tools for risk assessment in COVID-19 patients [ 122 , 123 , 124 , 125 ]. More recently, an interesting prospective multicenter study on hospitalized COVID-19 patients with respiratory failure showed that a larger neck circumference phenotype patient is more prone to have a negative outcome, a large neck being associated with an increased proinflammatory and prothrombotic status.…”
Section: Implications Of the Findings And Future Perspectivesmentioning
confidence: 99%